Characterization of Genes Associated with Gaharu Formation and Anatomical Changes in Stress-Induced Aquilaria Malaccensis Lam - Wong, Mun Theng (2010)
Aquilaria malaccensis (Karas) is a native tree that produces aromatic oleoresins (gaharu or agarwood) in response to external attack. Little is known about oleoresin synthesis in the wood. To understand this phenomenon, several candidate genes in oleoresin synthesis pathway were cloned and expression patterns determined at various time points after stress induction. Three genes were cloned in this study: two transcriptional factors from the WRKY family and a gene that encodes terpene synthase. A partial length cDNA of AmWRKY1 was isolated through RACE-PCR. The cDNA fragment was 871 bp and the deduced polypeptide consisted of 194 amino acids. The deduced protein sequence exhibited high sequence similarity (63-72%) to WRKY proteins from group I. The second WRKY gene which was designated as AmWRKY2 was 580 bp long. The translated sequence had poor similarity to other WRKY protein with only 36% similarity to Zinc-dependent activator protein-1 (Zap1) from Arabidopsis thaliana. The cloned terpene synthase fragment had a length of 344 bp and was designated as AmTPS1. The deduced protein exhibited 62-80% sequence similarity to known acyltransferases proteins. The expression profile of the three transcripts including phenylalanine ammonia-lyase (PAL) gene from a previous study in a 30 days cycle were investigated using real-time RT-PCR (qPCR). Expression of all the four transcripts was regulated differently from 3 hours to 30 days. AmWRKY1 and AmTPS1 showed immediate-early expression at 3 hours while AmWRKY2 and AmPAL were expressed later starting from 16 hours. In addition, the anatomical structures of juvenile and mature resinous wood were compared, and changes in the woody tissues were determined following mechanical wounding and electrical stimulation. There was no difference between juvenile and mature wood except that the percentage of area covered by included phloem in juvenile wood was twice than that of mature wood. In juvenile wood, the content of starch grains decreased in inner sapwood when compared to outer sapwood. In resinous wood, brownish bodies were found in both ray and axial parenchyma, included phloems, xylem vessels and fibers. From unstained sections of 48 hours following wounding of juvenile tree, brownish substance was found in ray parenchyma cells, included phloem and fibers. Electrical stimulation on 3-year old trees was carried out by applying doses of high voltage currents. After 28 days of electrical stimulation, naked eye observation revealed that the outer sapwood was dehydrated, while the inner sapwood was carbonized. Included phloems were crushed and the vessels of the affected wood contained brownish bodies. In addition, fungal hyphae were observed inside the carbonized area. In conclusion, the results of gene expression indicate that AmWRKY1, AmWRKY2, AmTPS1 and AmPAL may be involved in ‘gaharu’ formation. It can be deduced that wounding, either by direct penetration into the stem or by indirect damage through electrical shock, is the primary cause to commence synthesizing of gaharu. Both juvenile and mature wood, have the ability to produce oleoresin as there was no major anatomical difference between them. In this study, juvenile tree as young as 3-year old can produce oleoresin when given proper treatment.